Gonur, Maryskij Velajat, Turkmenistan - Boroffka, Nikolaus (e-Forschungsberichte des DAI, 2023)
The Bronze Age city-site of Gonur Depe in the Margiana has been excavated by V. I. Sarianidi and his team for many years. Since 2010 the Eurasia Department is taking part in the research. New work has been carried out in the eastern part of the city inside the surrounding wall, in an area just outside the northern gate of the city wall, where architecture and burials were discovered, as well as in outlying rural sites and by surveying the surroundings to around 10 km distance from the central city.